Insights from ADPedKD, ERKReg and RaDaR registries provide a multi-national perspective on the presentation of childhood autosomal dominant polycystic kidney disease in high- and middle-income countries - Gimpel, Charlotte; Fieuws, Steffen; Hofstetter, Jonas; Pitcher, David; Vanmeerbeek, Lotte; Haeberle, Stefanie; Dachy, Angélique; Massella, Laura; Seeman, Tomas; Ranchin, Bruno; Allard, Lise; Bacchetta, Justine; et al. (Kidney international, 2025)
Data on the presentation of Autosomal Dominant Polycystic Kidney Disease (ADPKD) in children have been based on small/regional cohorts and practices regarding both asymptomatic screening in minors and genetic testing differ greatly between countries. To provide a global perspective, we analyzed over 2100 children and adolescents with ADPKD from 32 countries in six World Health Organization regions: 1060 children from the multi-national ADPedKD registry were compared to 269 pediatric patients from the United Kingdom (RaDaR) and 825 from the European Rare Kidney Disease Registry (ERKReg). Asymptomatic family screening was a common mode of presentation (48% in ADPedKD, 62% in ERKReg) with broad international variability (19%-75%), but fairly stable temporal trends in both registries with no correlation to genetic testing. The national rates of genetic testing varied and correlated significantly with healthcare expenditure (odds ratio 1.030 per 100 United States Dollars/capita/year, in the ERKReg cohort), with little variation over time. Diagnosis due to prenatal abnormalities was more common than anticipated at 14% increasing steadily from 2000 onward in both registries. Realistically, a high proportion of children were diagnosed with ADPKD by active screening, underlining that families affected by ADPKD have a high need for counselling on the complex issues around presymptomatic diagnosis. Regional variations in rate of genetic testing appeared to be driven by economic factors. However, large differences in rate of active screening were not correlated to healthcare spending and probably reflect the influence of different of cultural, legal and ethical frameworks on families and clinicians in different healthcare systems.
Keywords: demographics; lidé; mladiství; children; registrace; United Kingdom; adolescents; Infant; prenatální diagnóza; Female; dítě; Evropa; Genetic Testing; Prenatal Diagnosis; Polycystic Kidney, Autosomal Dominant; genetic testing; registry; Adolescent; Humans; Spojené království; autosomal dominant polycystic kidney disease; Registries; předškolní dítě; Child, Preschool; polycystické ledviny autozomálně dominantní; genetické testování; mužské pohlaví; ženské pohlaví; Male; Europe; Child; kojenec